Evolution of alternative male morphotypes in oxyurid nematodes: a case of convergence?. (30th May 2014) - Jorge, F.; Perera, A.; Roca, V.; Carretero, M. A.; Harris, D. J.; Poulin, R.
Abstract Male dimorphism has been reported across different taxa and is usually expressed as the coexistence of a larger morph with exaggerated male traits and a smaller one with reduced traits. The evolution and maintenance of male dimorphism are still poorly understood for several of the species in which it has been observed. Here, we analyse male dimorphism in several species of reptile parasitic nematodes of the genus Spauligodon, in which a major male morph (exaggerated morph), which presents the traditional male morphological traits reported for this taxon, coexists with a minor morph with reduced morphological traits (i.e. reduced genital papillae) resembling more closely the males of the sister genus Skrjabinodon than Spauligodon major males. Because of the level of uncertainty in the results of ancestral state reconstruction, it is unclear if the existence of male dimorphism in this group represents independent instances of convergent evolution or an ancestral trait lost multiple times. Also, although the number of major males per host was positively correlated with the number of females, the same did not hold true for minor males, whose presence was not associated with any other ecological factor. Nevertheless, the existence of male dimorphism in Spauligodon nematodes is tentatively interpreted as resulting from alternative reproductive tactics, with differences in presence and number of individuals as indicators of differences in fitness, with the lower numbers of minor males per host likely maintained by negative frequency‐dependent selection.